The Teeny-Weeny Unicorn's great big wish - Harris, Shawn (New York : Alfred A. Knopf, 2025)
A tiny unicorn longing to be big takes one last chance to make his wish come true, and with a gust of lucky wind and a fairy princess, discovers an unexpected surprise.
K-3
AD570L
Keywords: Unicorns -- Juvenile fiction; Stature -- Juvenile fiction; Wishes -- Juvenile fiction; Fairies -- Juvenile fiction; Unicorns -- Fiction; Size -- Fiction; Wishes -- Fiction; Fairies -- Fiction